Working Memory Modulates Glutamate Levels in the Dorsolateral Prefrontal Cortex during 1H fMRS - Woodcock, Eric A.; Anand, Chaitali; Khatib, Dalal; Diwadkar, Vaibhav A.; Stanley, Jeffrey A. (Frontiers in Psychiatry, 2018)
Glutamate is involved in excitatory neurotransmission and metabolic processes related to brain function. Previous studies using proton functional magnetic resonance spectroscopy (1H fMRS) have demonstrated elevated cortical glutamate levels by 2-4% during visual and motor stimulation, relative to periods of no stimulation. Here, we extended this approach to working memory cognitive task performance, which has been consistently associated with dorsolateral prefrontal cortex (dlPFC) activation. Sixteen healthy adult volunteers completed a continuous visual fixation 'rest' task followed by a letter 2-back working memory task during 1H fMRS acquisition of the left dlPFC, which encompassed Brodmann areas 45 and 46 over a 4.5cm3 volume. Using a 100% automated fitting procedure integrated with LCModel, raw spectra were eddy current-, phase-, and shift-corrected prior to quantification resulting in a 32s temporal resolution or 8 averages per spectra. Task compliance was high (95% ± 11% correct) and the mean Cramer-Rao Lower Bound of glutamate was 6.9% ± 0.9%. Relative to continuous passive visual fixation, left dlPFC glutamate levels were significantly higher by 2.7% (0.32 mmol/kg wet weight) during letter 2-back performance. Elevated dlPFC glutamate levels reflect increased metabolic activity and excitatory neurotransmission driven by working memory-related cognitive demands. These results provide the first in vivo demonstration of elevated dlPFC glutamate levels during working memory.